Modelisation de la Dynamique du Trait de Cote sur une Portion de la Cote Ouest Cameroun Allant de Batoke a Seme Beach par Imagerie Landsat de 1979 a 2018 - Arnaud, Kouekam Kengap; Gustave, Fowe Paul; Fulbert, Togue Kamga; Romain, Ngueguim Jules; Stephan, Tsague Junior (European Scientific Journal, ESJ, 2019)
The general objective of this study is to contribute to the actual and future acknowledging of the coastline dynamics of a portion of the WestCameroon coast using Landsat satellite images 3, 7 and 8 from 1979 to 2018. To achieve this objective, the images were pre-treated through atmospheric corrections using the ENVI 5.1 software, which enabled the digitalization of the coastlines of the study zone in the different images using the ArcGIS version 10.1 software and then the statistical computation of the speeds of evolution of the coastline at different dates was done using DSAS version 4.3. The main results obtained show two evolutionary trends of coastal linear interest: in the long term, the study has given a decline in the coastline of an annual average rate equal to -1.09 m/year between 1979 and 2018 and in the medium term, the study shows an advance of the coastline with an average speed of evolution equal to +0.75 m/year between 2000 and 2018. In the same period, the zone experienced a short-term constant erosion between 2000-2005 and 2005-2008 with an average rate of -1.12 m/year, a slight stability between 2008 and 2012 with a speed of -0.08 m/year, while from 2012 to 2016 it has undergone an average evolution of +2.44 m/year. A forecast of the phenomenon in 2028 has given a coastline position of 10.90 m compared to its current position, which could jeopardize hotel infrastructure such as: Seme Beach Hotel; Madison Beach; Etisah Beach and the fishing camps of Batoké village during episodes of high tide. La présente étude a pour objectif général de contribuer à la connaissance actuelle et future de la dynamique du trait de côte d’une portion de la côte Ouest-camerounaise à l’aide des images satellitaires Landsat 3, 7 et 8 de 1979 à 2018. Pour atteindre cet objectif, les images ont subi un prétraitement à travers des corrections atmosphériques à l’aide du logiciel ENVI 5.1; ce qui a permis la digitalisation destraits de côtes de la zone d’étude contenus dans les différentes images à l’aide du logiciel ArcGIS version 10.1 puis le calcul statistique des vitesses d’évolution du trait de côte à différentes date s’est effectué à l’aide de DSAS version 4.3. Les principaux résultats obtenus nous montrent deux tendances évolutives du linéaire côtier d’intérêt : sur le long terme, l’étude a donné un recul du trait de côte d’un taux moyen annuel égal à -1,09 m/an entre 1979 et 2018 et à moyen terme, l’étude montre une avancée du trait de côte avec une vitesse moyenne d’évolution égale à +0,75 m/an entre 2000 et 2018. Dans cette même période, la zone a connu à court terme une situation constante d’érosion entre 2000-2005 et 2005-2008 avec un taux moyen de -1,12 m/an, une légère stabilité entre 2008 et 2012 avec une vitesse de -0,08 m/an, tandis que de 2012 à 2016, elle a subi un engraissement en moyenne de +2,44 m/an. Une prévision du phénomène en 2028 a donné une position du trait de côte de 10,90 m par rapport à sa position actuelle, ce qui pourrait mettre en péril des infrastructures hôtelières telles que : Seme Beach Hôtel ; Madison Beach ; Etisah Beach et les campements des pêcheurs du village Batoké pendant les épisodes de marées de vives eaux.